Investing in Sub-Saharan Africa: The Role of Internal Macroeconomic Factors and Institutional Quality in FDI Growth - (:unkn) unknown (My University, 2025)
The level of foreign direct investment drawn by developing countries like those in the sub-Saharan Africa is influenced by various internal macroeconomic factors and internal institutional indicators inherent in the specific country or region. However, FDI inflow to Sub-Sahara African (SSA) region are much lower when compared to countries in other regions of the world due to lack of investor confidence in Sub-Saharan Africa's economic prospects and investment climate characterized by institutional weakness and macroeconomic instability. Therefore, this study aimed at examining the effect of internal macroeconomic factors and internal institutional quality indicators on foreign direct investment in Sub-Sahara Africa. The study adopted ex-post facto research design. Top 10 recipients of FDI in Sub-Sahara Africa formed the sample of the study. Data were sourced from World Governance Indicators (WGI) and World Development Indicators (WDI) between 1996 and 2023. To address the problem of endogeneity in the dataset, the study employed dynamic panel autoregressive distributive lag (PARDL) model for the analysis. The results showed that trade openness, foreign reserve, exchange rate and regulatory quality have significant short- and long-run positive effects on FDI, while external debt, political stability and control of corruption have significant short- and long-run negative effects on FDI. The study concluded that internal macroeconomic and institutional factors affect FDI in sub-Saharan Africa. Therefore, the study recommended that investors should focus on investing in Sub-Saharan African countries with stable macroeconomic environments, strong institutional frameworks, and policies that promote trade openness, regulatory quality, and political stability, as these factors create the most favourable conditions for long-term investment growth.
Keywords: African Research